Reviving Taman Tasik Seri Serdang, Selangor as an edu-eco park for community well-being through environmental design approach - Salahuddin, Amanina (2018)
Park and open space give so many advantages for human beings like for integration and socialization, human well-being, economic and environmental. The objective of the study is to rejuvenate Taman Tasik Seri Serdang as a heart of community area to connect Universiti Putra Malaysia (UPM), Serdang commercial area and residential to become livable Serdang Green Town. By analyzing Taman Tasik Seri Serdang, there are some main issues that related to design such as underutilized green space, insufficient public facilities-jogging track and bicycle lane as well as space for rollerblade and inadequate of connectivity between nodes, greatest extent users to enter the park ; potential green space area not well expanded and utilised, lack of space for outdoor activity and no special characteristics and a potential of eco linear linkage for institutional and residential purposes. Edu-eco park is picked as a concept for my landscape design by offering more facilities and activities that interconnected to education and environmental design approach towards Taman Tasik Seri Serdang. This concept is to enhance the lake park that is related to human activities and the current biodiversity and ecosystem in consideration to provide a solution to the inadequate of connectivity, underutilisation of green space and lack of space for outdoor activity users. Hence, it believes strongly this 850 m perimeter of lake park can maintain and sustain for up- coming genesis and to be a new tourist spot and transit focusing at institutional areas and public park as also a landmark in 2020 together with the first Edu-eco park in Selangor.